THE CONCEPT OF COMPETENCE IN THE CONTEXT OF EDUCATION REFORM IN LATVIA - Briška, Ilze; Siliņa-Jasjukeviča, Gunta; Kalēja-Gasparoviča, Daiga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The word competence is a key concept of ongoing education reform in Latvia - the ESF project “Competency approach in the curriculum” (hereafter: Project). The implementation of the idea of competence-based curriculum is related to significant changes in the structure of school and pre-school curriculum, the system of evaluation of learning outcomes, teacher education etc., which are widely clarified and discussed in expert groups and public space. Participating as experts in the development of a Project, the authors of the article find that the Latvian educational space lacks a common understanding of the meaning of the concept competence. Often the pedagogical terminology used by educators even contradicts the innovative meaning and essence of the reform. The aim of the article is to clarify the inconsistency and contradictions related to understanding of the concept competence in the context of Latvian educational reforms. Research question: How to use the pedagogical terminology related to concept competence to reflect the innovative approach correctly and deeply, but at the same time - simple and understandable for the teachers, parents and children. To find it out, the article analyzes the essence of the competence approach in theory and compares it with the actual situation in practice. The research data were obtained in 34 written students’ reflections after study practice and 9 interviews with experienced teachers of general education schools in different regions of Latvia. The content analysis of the interviews was proceeded, the dimensions of holistic understanding of concept competence was marked and types of contradictions – generalized. Results: The analysis revealed discrepancies between terminology used in the framework of educational reform, and educators’ understanding of its meaning. These findings can develop educators’ common understanding of concept ‘competence’.